Relationship between emotional intelligence and quality of healthcare among nurses - Oweidat, Islam; Alzoubi, Mahmoud; Shosha, Ghada Abu; Ta’an, Wafa’a; Khalifeh, Anas; Alzoubi, Majdi M.; Al-Mugheed, Khalid; Alabdullah, Amany Anwar Saeed; Abdelaliem, Sally Mohammed Farghaly (Frontiers in Psychology, 2024)
Introduction: Healthcare organizations are operating worldwide facing steep and survival competition in a changing environment.Objectives: To examine the relationship between emotional intelligence and quality of healthcare among Jordanian nurses in governmental hospitals.A descriptive correlational design utilizing a sample of 172 nurses.Participants of this study using online self-administered questionnaires from five governmental hospitals in Jordan, participants filled out and submitted the online nurse-assessed quality of nursing care scale and Genos emotional intelligence concise scale in addition to the socio-demographic data.Results: Nurses' participants demonstrated a high level of emotional intelligence (M = 3.809, SD ± 0.484), and a very high level of quality of healthcare (M = 4.260, SD ± 0.372). There was a statistically significant correlation between the total of quality of healthcare variable and the total of emotional intelligence variable amounted to (r=0.739, P<0.01). There was a statistically significant correlation between the total of quality of healthcare and emotional intelligence variables each with its dimensions. In which, (r = 0.357-0.739). Emotional intelligence variable was able to predict the quality of healthcare, in which (F = 34.872, P ≤0.001). There is a positive correlation between the two variables amounted to (r=0.733). In addition, emotional intelligence explains the amount of (59.8) of the variation in the quality of healthcare.Conclusions: Emotional intelligence is a key predictor of quality of healthcare.Emotional intelligence is important concept to be considered in recruiting, staffing, promoting, and developing employees, as a superiority criterion in healthcare organizations.